2022
DOI: 10.1371/journal.pone.0263563
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive deletions in a unique Uruguayan SARS-CoV-2 lineage evidence the genetic variability potential of accessory genes

Abstract: Deletions frequently occur in the six accessory genes of SARS-CoV-2, but most genomes with deletions are sporadic and have limited spreading capability. Here, we analyze deletions in the ORF7a of the N.7 lineage, a unique Uruguayan clade from the Brazilian B.1.1.33 lineage. Thirteen samples collected during the early SARS-CoV-2 wave in Uruguay had deletions in the ORF7a. Complete genomes were obtained by Illumina next-generation sequencing, and deletions were confirmed by Sanger sequencing and capillary electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Although highly variable in position and length, frameshift deletions that induce truncation of accessory protein 7a are not unique. There are numerous independent occurrences of such a mutation across both A and B lineages of SARS-CoV-2, including among VOCs [31][32][33][34][35][36][37][38] . Global genomic surveillance of SARS-CoV-2 has shown that mutations frequently occur at the downstream regions of ORF7a with such changes often leading to premature stop codons resulting in protein products with reduced functional activity.…”
Section: Discussionmentioning
confidence: 99%
“…Although highly variable in position and length, frameshift deletions that induce truncation of accessory protein 7a are not unique. There are numerous independent occurrences of such a mutation across both A and B lineages of SARS-CoV-2, including among VOCs [31][32][33][34][35][36][37][38] . Global genomic surveillance of SARS-CoV-2 has shown that mutations frequently occur at the downstream regions of ORF7a with such changes often leading to premature stop codons resulting in protein products with reduced functional activity.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 has accumulated many variations since its emergence in late 2019 [ 21 ]. Nucleotide substitutions that produce amino acid replacements constitute the primary raw material for genetic variation; however, many insertions and deletions (indels) are likely to be critical elements in coronavirus macro- and microevolution [ 22 , 23 , 24 , 25 , 26 , 27 ]. Although most indels negatively affect viral fitness, a small number of them emerged and spread in viral populations, suggesting a positive effect on viral fitness and adaptive evolution [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that single and large deletions in accessory genes may create changes in genome organization to cause more virus fitness. [30][31][32] We detected 30 and 15 consecutive deleted amino acids in Pts 7 and 9.…”
Section: Sars-cov-2 Genome Analysismentioning
confidence: 86%